Exploring need dynamics within and across days in everyday life: a three-level analysis - Neubauer, Andreas B.; Voß, Andreas; Ditzen, Beate (Journal of research in personality, 2018)
People experience frustration of their basic psychological needs (autonomy, competence, relatedness) in daily life, but does this frustration trigger motivation to restore this need and, in turn, to attain need satisfaction? The present study explored the temporal dynamics of need dissatisfaction, motivation, and satisfaction in an ecological momentary assessment (N=58; ten daily assessments of need satisfaction, dissatisfaction and motivation for five days). While need dissatisfaction did not predict need motivation overall, need motivation predicted need satisfaction within a day for competence, and across days for relatedness. Potential explanations for this pattern of results are discussed. Findings emphasize the importance of specifying the time frame over which dynamic effects evolve and acknowledging differences between the needs.
Gesehen am 17.02.2020